Turnover Study of Heparin Cofactor II in Healthy Man - Sié, P; Dopouy, D; Pichon, J; Boneu, B (Thrombosis and Haemostasis, 1985)
Heparin cofactor II (HC II) is a heparin-dependent inhibitor of thrombin, distinct from antithrombin III (AT III). This study was designed to evaluate its metabolism in healthy subjects. Purified HC II was labelled with 125I by the lactoperoxidase-glucose oxidase technique. The biological activity of the HC II was unchanged after labelling as was its migratory pattern by crossed immunoelectrophoresis in the presence of heparin or dermatan sulfate.Three healthy volunteers were injected with 10 uCi and the plasma radioactivity was measured daily. The data were approximated by a sum of two exponential terms and the metabolism of HC II was described by a two compartment mamillary system.The mean values of fractional catabolic rate, intravascular fraction and half-life of the elimination phase were respectively: 0.44 d-1, 0.60 and 2.53 d. These parameters are of the same order of magnitude as those reported in the literature for AT III. The plasma HC II concentration in the 3 subjects ranged from 61 to 82 ug/ml as estimated using our purified preparation. Accordingly, the absolute catabolic rate ranged from 1.17 to 1.36 mg · kg-1 · d-1.
Keywords: Heparin cofactor II; Metabolism